Pan-cancer vaccines: breaking tolerance by targeting stress-induced post-translational modifications in tumours - Atabani, Suha (2023)
Cancer immunotherapy aims to induce potent pro-inflammatory immune responses that can lead to elimination of tumours. The challenge of this approach is to induce cancer-specific immune responses that do not cross react with healthy tissues and are not subject to the anti-inflammatory suppressive tumour environment. One approach is to use a vaccine therapy that targets cancer-associated antigens.